Kinetic analysis of the inhibitory effect of trichloroethylene (TCE) on nitrification in cometabolic degradation - KOCAMEMİ, BİLGE (SPRINGER, 2007)
In this study, the inhibitory effect of TCE on nitrification process was investigated with an enriched nitrifier culture. TCE was found to be a competitive inhibitor of ammonia oxidation and the inhibition constant (K-I) was determined as 666-802 mu g/l. The TCE affinity for the AMO enzyme was significantly higher than ammonium. The effect of TCE on ammonium utilization was evaluated with linearized plots of Monod equation (e.g., Lineweaver-Burk, Hanes-Woolf and Eadie-Hofstee plots) and non-linear least square regression (NLSR). No significant differences were found among these data evaluation methods in terms of kinetic parameters obtained.
Keywords: cometabolism; kinetics; modelling; nitrification; trichloroethylene; GEL-ELECTROPHORESIS DGGE; NITRIFYING BACTERIA; IN-SITU; NITROSOMONAS-EUROPAEA; CHLORINATED SOLVENTS; MIXED CULTURE; METHANE; BIODEGRADATION; AMMONIA; TRANSFORMATION